(untitled) (Third Sector Social Economic Review, 2024)
Social Network Analysis allows for the investigation of social structures and the identification of social positions of all actors within a network. Organizational network emerged as a concept as a consequence of examination of social network analysis concepts and methods at the business level at intra-business or inter-business dimensions. In today’s tough global competitive environment, organizations continue their activities in constant mutual relations with all their other stakeholders in many areas, especially in the social and economic fields, and organizational networks are formed within the framework of these relationships. Organizational network structures analyze and interpret a company’s relationships with other businesses and stakeholders within the same network and help the company to position itself strategically. The rise of social networking systems, globalization, and the expansion of the Internet have underscored the importance of social network analysis. This analytical approach has been instrumental in examining social relationships across various scales, actors, and structures, providing valuable insights in today’s interconnected world. This study delves into the basic concepts of social network analysis, widely used in the interdisciplinary field, and offers comprehensive evaluations of the literature on organizational networks with a systematic literature review.